Treatment-Related Toxicity Using Prostate-Only Versus Prostate and Pelvic Lymph Node Intensity-Modulated Radiation Therapy: A National Population-Based Study - Parry, Matthew G. (J Clin Oncol, 2019)
PURPOSE: There is a debate about the effectiveness and toxicity of pelvic lymph node (PLN) irradiation for the treatment of men with high-risk prostate cancer. This study compared the toxicity of intensity-modulated radiation therapy (IMRT) to the prostate and the pelvic lymph nodes (PPLN-IMRT) with prostate-only IMRT (PO-IMRT). MATERIALS AND METHODS: Patients with high-risk localized or locally advanced prostate cancer treated with IMRT in the English National Health Service between 2010 and 2013 were identified by using data from the Cancer Registry, the National Radiotherapy Dataset, and Hospital Episode Statistics, an administrative database of all hospital admissions. Follow-up was available up to December 31, 2015. Validated indicators were used to identify patients with severe toxicity according to the presence of both a procedure code and diagnostic code in patient Hospital Episode Statistics records. A competing risks regression analysis, with adjustment for patient and tumor characteristics, estimated subdistribution hazard ratios (sHRs) by comparing GI and genitourinary (GU) complications for PPLN-IMRT versus PO-IMRT. RESULTS: Three-year cumulative incidence in the PPLN-IMRT (n = 780) and PO-IMRT (n = 3,065) groups was 14% for both groups for GI toxicity, and 9% and 8% for GU toxicity, respectively. Patients receiving PPLN-IMRT and PO-IMRT had similar levels of severe GI (adjusted sHR, 1.00; 95% CI, 0.80 to 1.24; P = .97) and GU (adjusted sHR, 1.10; 95% CI, 0.83 to 1.46; P = .50) toxicity rates. CONCLUSION: Including PLNs in radiation fields for high-risk or locally advanced prostate cancer is not associated with increased GI or GU toxicity at 3 years. Additional follow-up is required to answer questions about its impact on late GU toxicity. Results from ongoing trials will provide insight into the anticancer effectiveness of PLN irradiation.